Human-centered artificial intelligence : research and applications - Nam, Chang S.; Jung, Jae-Yoon; Lee, Sangwon, 1979- (Academic Press, 2022)
"Human-Centered Artificial Intelligence: Research and Applications presents current theories, fundamentals, techniques and diverse applications of human-centered AI. Sections address the question, 'are AI models explainable, interpretable and understandable?', introduce readers to the design and development process, including mind perception and human interfaces, explore various applications of human-centered AI, including human-robot interaction, healthcare and decision-making, and more. As human-centered AI aims to push the boundaries of previously limited AI solutions to bridge the gap between machine and human, this book is an ideal update on the latest advances."--Publisher's website.